PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE SCRAMBLE UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SD NEGERI 188 PEKANBARU - Hesty Anggraini; Eddy Noviana; Lazim N ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research was carried out because of the lowlearning outcomes of social studies of grade IV in SD Negeri 188 Pekanbaru, KKM (success criteria) assigned in school, that is 78. The class consist of 32 students, who reached the KKM is just 14 students (43.75%), whereas students who have not yet reached the KKM is 18 students (56.25%) with average rating of class 63.75. To solve these problems then the researchers implement scramble cooperative learning model. The purpose of this research is to improve the learning achievement of social studies of grade IV in SD Negeri 188 Pekanbaru with the implementation of the scramble cooperative learning model. The result of this research shows that the average value of basic score is 63.75 and increased in cycle I from 13.54% become 72.38. In cycle II, the average value of the students also increase 36.29% become 86.88. The development of group at the first meeting cycle I there are 2 groups get category of good, 3 groups get category of very good, and 1 group get special category. And on the next meeting there are 2 group get category of very good and4 groups get special category. On a basic score of students classical success criteria of social studies is 43.75% (not completely). After implementation of scramble cooperative learning model on cycle 1, number of success criteria of students classical learning increased become 59.38% (not completely). And on cycle II, success criteria of students classical learning increased by 87.50% (completely). Then, the activity of the teacher on the first meeting of the cycle 1 got was 58.33% by category is enough. The second meeting was increased become 75.00% with category of good. on the first meeting of the cycle II teacher activity increased become 83.33% by category of very good. At the second meeting increased become 91.66% with the very good category. The activity of the students at the first meeting of the cycle I got was 54.16% by category of enough. The second meeting was increased become 66.66% with category of good. At the first meeting of the cycle II activity of students increased become 75.00% with category of good. At the second meeting increased become 83.33% by very good category. From this research it can be concluded that by implementation of the scramble cooperative learning model can improve students learning outcomes of social studies of grade IV in SD Negeri 188 Pekanbaru.Keywords: Scramble Cooperative Type, Social Studies Outcomes